RELATIONSHIP BETWEEN HABIT IN WATCHING ENGLISH MOVIES AND VOCABULARY - Anastasia, Paula; M. Said, Mawardin; Maf'ulah, Maf’ulah (Tadulako University, 2023)
This research aimed to identify the relationship between habit of watching English movie and vocabulary of grade VIII students' at SMP Negeri 6 Palu. It applied correlation research with a quantitative data approach. Students of Class VII-A, which consisted of twenty-five students, were selected as the sample for this research using the purposive sampling technique. The instruments of this research were questionnaires, vocabulary tests, and the SPSS 26th version. The result of data analysis using the correlation coefficient product moment and SPSS 26th indicated the relationship between students' habit in watching English movies and vocabulary is positive in the high category of relationship (0,702) with a significant level (α = 0.05). Then, comparing the value of the r-counted, which is higher than the r-table, indicates that students' habits of watching English movies contribute to their vocabulary. Therefore, students with a high frequency of habits in watching English movies have a higher probability of gaining a lot of new vocabulary.